Inhibition of DNA synthesis by an electrophilic metabolite of benzo[a]pyrene. - Busbee, D L (1984)
Mitogen-stimulated scheduled DNA synthesis and DNA excision repair in human lymphocytes, as well as DNA polymerase a activity in a cell-free system, were inhibited by an electrophilic metabolite of benzo[a]pyrene. This metabolite, (+/-)-anti-(7r,8t)-dihydroxy-(9,10t)-epoxy-7,8,9,10-tetrahyd robenzo[a]pyrene (BPDE), covalently binds to cellular macromolecules and is mutagenic, carcinogenic, and cytotoxic. Human lymphocytes treated with BPDE at concentrations greater than 500-800 ng/ml showed decreases in both mitogen-stimulated DNA synthesis and excision repair of damaged DNA but did not exhibit overt cytotoxicity (excluded trypan blue and maintained an adenylate charge of greater than 0.7). Formation of, and total concentration of, BPDE-DNA adducts was not correlated with inhibition of DNA synthesis. DNA polymerase alpha studies using a cell-free system showed that enzymatic activity was not diminished when purified polymerase was treated with BPDE prior to the addition of template DNA. When the template DNA concentration was varied, BPDE inhibition of enzyme activity was uncompetitive. BPDE inhibition of enzyme activity was found to be noncompetitive when concentrations of dATP, dCTP, or dTTP were varied and competitive when the concentration of dGTP was varied. The data indicate that BPDE competitively inhibits interaction of dGTP with the template-DNA polymerase alpha complex.